EDUKASI STOP BULLYING SEBAGAI STRATEGI MEMBANGUN SEKOLAH RAMAH ANAK DI SD NEGERI 3 BANGKIR - Nurul Asma; Moh Rudini; Naraya Zikra Rukhsana; Selviana Eka Safitri Karaeng; Rivani Rivani; Moh. Yusuf Habi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
This community service is motivated by the rampant cases of bullying in elementary schools that can disrupt the psychological, social, and academic development of students. The purpose of this community service is to describe the implementation of Stop Bullying education as a strategy to build a child-friendly school at SD Negeri 3 Bangkir. The community service uses a qualitative approach with descriptive methods. Data were collected through observation, interviews with teachers and students, and documentation of activities. The results of the community service show that the Stop Bullying education program is implemented through socialization, thematic learning, and extracurricular activities that instill the values ​​of tolerance, empathy, and skills to resolve conflicts without violence. In addition, the support of teachers, principals, and parents plays an important role in the success of the program. The community service findings indicate that Stop Bullying education is able to reduce the intensity of bullying, increase student awareness of the impact of Bullying, and create a safer, more inclusive, and child-friendly school environment. Thus, this strategy can be a model for implementation in other elementary schools to realize character-based education and protect children's rights.